KALIKORVA STRUCTURE AND ITS POSITION IN THE SYSTEM OF THE NORTHERN KARELIAN GREENSTONE BELTS: GEOCHEMICAL AND GEOCHRONOLOGICAL DATA - Mil'kevich R.I.; Myskova T.A.; Glebovitsky V.A.; L'vov A.B.; Berezhnaya N.G. (My University, 2007)
New geochemical data on volcanic rocks and the first U-Pb zircon ages for the Kalikorva structure made it possible to determine the time and conditions of their formation and constrain geodynamic models. The lower sequences of the Kalikorva structure is dominated by metatholeiites with high MgO, Cr, and Ni contents, high Mg#, and REE distribution patterns close to the mantle level. They contain rare komatiite interlayers and lenses of pyroxenites and peridotites and can be considered as products of the deep melting of mantle material. At the same time, the tholeiitic metabasalts bear island-arc signatures and are intercalated with metagraywackes and metadacites (adakites). This rock association could be formed under spreading conditions at the beginning of an island-arc regime. The upper sequence is dominated by metagraywackes and contains diverse rocks with both MORB (tholeiitic and komatiitic basalts) and island-arc (calc-alkaline andesite and dacites, subalkaline basalts, and picritic basalts) affinity, which is typical of back-arc basins. The U-Pb dating of zircons from the metadacites and detrital zircons from the metagraywackes of the Kalikorva structure yielded similar ages of 2785 ± 13 and 2766 ± 21 Ma, respectively. They coincide with the age of the late volcanic complex of the Hisovaara Group of the Hisovaara structure (2780 Ma). Both complexes include island-arc associations with subduction signatures and contain adakites, Nb-Ti basalts, and basaltic andesites. The metagraywackes and metadacites of the Chupa sequence of the Belomorian mobile belt are older than the similar rocks of the Kalikorva complex and have an age of 2870 ± 30 Ma. Ages of 2735 ± 20 Ma and 2720 ± 4 Ma were previously obtained for the metaandesites of the Kichany volcanogenic complex, which could be an even younger volcanic arc.
Keywords: Precambrian::Archean::Neoarchean; Докембрий::Архей::Неоархейская